Innovation incentives and competition for corporate resources - Dutta, Sunil; Fan, Qintao (Review of Accounting Studies, 2025)
This paper investigates how competition for scarce corporate resources impacts innovation incentives within multidivisional firms and, consequently, shapes firms’ preferences for fostering or restricting intra-firm competition. In our model, divisions become privately informed about the potential value of new investment opportunities generated through their innovation initiatives. We demonstrate that intra-firm competition unambiguously reduces divisions’ ex ante innovation incentives. However, it benefits ex post resource allocation by enabling the firm to (i) select the most promising project and (ii) limit the rents divisions earn from their private information. Consequently, a firm’s preference to limit or encourage interdivisional competition hinges on balancing ex post allocative efficiency, which favors increased intra-firm competition, against ex ante innovation incentives, which favor reduced competition. Our analysis identifies plausible conditions under which each organizational design—competitive or exclusive innovation—emerges as the optimal choice.